Assessing knowledge of dental house officers regarding dosage calculation and complications of local anaesthesia, in three tertiary care dental hospitals of DUHS, Karachi - Zamarud, Wania; Ashraf, Aisha; Qazi, Muhammad Saud; Waseem, Neha; Shaikh, Amynah Charania; Ahmed, Tehniat Faraz (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the knowledge and awareness of dental house officers regarding calculation of local anaesthesia dosage, and to evaluate differences in practices at various tertiary care facilities. Method: The cross-sectional study was conducted at three dental hospitals affiliated with Dow University of Health Sciences, Karachi from July to December 2022, and comprised house officers of either gender currently enrolled at the participating centres. Data was collected using a self-administered questionnaire to assess knowledge and awareness of local anaesthesia dosage calculation, administration methods, and common complications. Data was analysed using SPSS 26. Results: Of the 200 subjects approached, 136(68%) responded, and 89(65.4%) of them were females. Knowledge regarding the meaning of 2% lidocaine solution was low 45(33%), and 68(50%) subjects were knowledgeable about the maximum dosage of lidocaine with epinephrine. In terms of practice, lidocaine was the most commonly administered local anaesthetic 115(85%), followed by bupivacaine 15(11%). The majority of subjects administered local anaesthesia with vasoconstrictor 127(94%), but only 36(27%) performed aspiration during administration. Syncope 71(52%) was the most commonly reported complication, followed by lip/cheek/tongue biting by 35(26%). Conclusion: House officers’ knowledge level of local anaesthesia administration indicated the need for adequate training. Key Words: Local anaesthetics, Knowledge, Lignocaine, Drug dosage calculation.